Foundations for an Electronic Medical Record - Rector, A. L.; Nowlan, W. A.; Kay, S. (Methods of Information in Medicine, 1991)
Given the many efforts currently under way to develop standards for electronic medical records, it is important to step back and reexamine the fundamental principles which should underlie a model of the electronic medical record. This paper presents an analysis based on the experience in developing the PEN & PAD prototype clinical workstation. The fundamental contention is that the requirements for a medical record must be grounded in its use for patient care. The basic requirement is that it be a faithful record of what clinicians have heard, seen, thought, and done. The other requirements for a medical record, e.g., that it be attributable and permanent, follow naturally from this view. We use the criteria developed to re-examine Weed’s Problem Oriented Medical Record and also relate the criteria to secondary uses of the medical record for population data, communications and decision support.
Keywords: Medical Record; Information Models; Standards; Problem-Oriented Medical Record